Photography and Classification of Information:: Proposed Framework for Graffiti Art - Novak, David (Street Art & Urban Creativity, 2015)
Street and urban creativity is a global phenomenon and graffiti art is one of its manifestations. This article briefly discusses some approaches to photography as to one of the main visual research methods in the research of graffiti art works. Moreover, a framework for the classification of information contained in photographs of graffiti art works is proposed. A three level system of classification is introduced based on a provided example.